EKSTRAKSI FITUR AKSARA BALI MENGGUNAKAN METODE ZONING - Darma, I Wayan Agus Surya; Putra, I K. G. Darma; Sudarma, Made (Majalah Ilmiah Teknologi Elektro; Vol 14 No 2 (2015): (July - December) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2015.v14i02p09)
Feature extraction is an important process in character recognition system. The purpose of this process is to obtain special feature from a character image. This paper is focuses on how to obtain special feature from a handwritten Balinese character image using zoning . This algorithm dividing Balinese character image into multiple regions, then a special feature on each region resulting the data extracted feature. The test result in this paper generates a various  semantic and direction feature data. This is because this paper using handwritten Balinese character. Furthermore, the features that produced in this paper can be used on Balinese character image recognition process
Keywords: Feature extraction, character, Balinese character, zoning, feature